Skrining fitokimia dan uji aktivitas antioksidan ekstrak etanol daun alpukat (Persea americana Mill.) dengan metode DPPH - Rahmah, Ruhiya; Rahayu, Rahayu; Ridwanto, Ridwanto; Daulay, Anny Sartika (Journal of Pharmaceutical and Sciences, 2023)
Indonesia is a country that is famous for its wealth of natural energy sources and plants that have medicinal properties. Avocado is one of the plants that residents have used from generation to generation for traditional medicine. Avocado (Persea americana Mill.) is a plant that contains many compounds that have antioxidant properties. Secondary metabolite bioactive compounds that play a role are saponins, alkaloids, flavonoids, steroids, safrole, and tannins. Antioxidant compounds are electron distributors, which can counteract oxidants' negative impacts. This research aims to determine the ethanol extract content of avocado leaves containing secondary metabolites and the IC50 value of avocado leaf extract. One method of measuring free radicals by antioxidant compounds is to use the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with a UV-Vis spectrophotometer at a wavelength of 516 nm and vitamin C as a comparison. The research showed positive results in the phytochemical screening of Simplicia and avocado leaf extract against alkaloids, flavonoids, tannins, steroid saponins, and glycosides. It can be concluded that the results of research on the antioxidant activity of avocado leaves have an IC50 value of 9.24 µg/ml in the very strong category, equivalent to vitamin C comparison, which has antioxidant activity with an IC50 value of 1.942 µg/ml in the very strong category.